IMPLIKASI TAFSIR KLASIK TERHADAP SUBORDINASI GENDER: PEREMPUAN SEBAGAI MAKHLUK KEDUA - Shinta Nurani (MUWAZAH : jurnal kajian gender, 2015)
Discriminatory views about women in the classical interpretation of the Qur’an such as the Qur’anic interpretation ofal-Suyuti, al-Baidhawi, Ibn Kathir, al-Qurtubi, and each other,places womenas being the second creation and the second sex. The logical consequenceofthisQur’anic interpretations which is produce a stigma that women do not deserve to be a certain tasks because women are weak creatures who often relies on men and the second sex after male. The effect of this viewsettlesin the subconscious so that it becomespublic knowledge that the women is subordination ofmen. Therefore we need are contextualization visionary interpretation of gender to realize the mission of the Qur’an as anideal guidance in life, perfect religious, and rahmatan lil Alamin.